Between Russia and a Hard Place: Great Power Grievances and Central Asian Ambivalence. Issue 10 (26th November 2018) - Radnitz, Scott
Abstract: This essay asks how Central Asian states have responded to Russia's intervention in Ukraine and salvos against the West, as a means to assess how Russia and the Central Asian states understand their national interests and exercise state power. It argues that the post-Soviet region shares a cynical and geopolitically driven view of the exercise of global power. Yet Russia has sometimes deployed its resources to advance short-term ideological objectives, whereas Central Asian foreign policy is pragmatic and opportunistic. The Ukraine crisis threatened to coerce the Central Asian states into conformity with Russia's interests; ironically, their dependence on Russia has enabled their freedom of action in foreign policy, within limits. The essay highlights the ways that geography enables and constrains the execution of foreign policy, and considers the ambiguous role ideology plays in the formulation of national interests and the prospects for international cooperation.